Preliminary Analysis of Life Cycle Assessment on Single-Use Plastic Cutlery Set Substitutes in the Catering Industry - Muhammad Ainul Fahmi; Maghfur Rozudin; Suci Oktaviani Putri; Jani Rahardjo (Pusbindiklatren Bappenas, 2023)
Single Use Cutlery plastic is an item easily obtained from food catering packages, such as tableware and cutlery sets from the catering industry and is very harmful to the environment. Therefore, this study conducted a Life Cycle Assessment (LCA) analysis to identify the key factors influencing the replacement of single-use cutlery sets within the catering industry. Data collected from the catering industry in Surabaya were processed using SEM PLS modeling. The results showed that the factors Goal and Scope Definition, Life Cycle Inventory, Impact Assessment, and Result Interpretation impact the Life Cycle Assessment of the Catering Industry in Surabaya City as evidenced by all p-values of the inner model being less than 0.05.